2010
DOI: 10.4995/wrs.2010.5883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inulin supplementation and age on growth performance and digestive physiological parameters in weaned rabbits

Abstract: Three diets were formulated, a control diet (C, 40.7% NDF, 15.1% CP), the same diet but medicated (M, 500 mg/kg oxytetracycline and 50 mg/kg thiamulin), and a third diet obtained substituting 4% of barley with inulin (Frutafi t) in C diet (I). Pannon White does and their litters were randomly allocated into three groups (8/group) at 21 d of lactation and diets offered to the does and kids from 21 d of lactation onwards. After weaning (28 d), growing rabbits (30 cages/ treatment, 2 rabbits/cage) were fed the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…As there are contradictory results in the literature, regarding the effect of inulin-type fructans on caecal microbial activity (Bónai et al, 2010), further research should focus on confirming the beneficial effect of dietary fructans on the digestive health of growing-fattening rabbits raised on commercial farms. The mode of fructan action should also be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there are contradictory results in the literature, regarding the effect of inulin-type fructans on caecal microbial activity (Bónai et al, 2010), further research should focus on confirming the beneficial effect of dietary fructans on the digestive health of growing-fattening rabbits raised on commercial farms. The mode of fructan action should also be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In rabbits, it has been shown that a diet containing inulin-type fructans affects the caecal microbial activity, morbidity and growth rate in a beneficial way (Morisse et al, 1993;Maertens et al, 2004;Volek et al, 2005Volek et al, , 2007Eiben et al, 2008) or not (Bónai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Radwan and Abdel-Khalek (2007) reported that advisable to fortify rabbit diets reared under elevated ambient temperatures with the prebiotics (galactooligosaccharide GOS â and Bio-Mos â ) supplementation improve growth and health of growing rabbits under high ambient temperature conditions. However, Bonai et al (2010) showed that Inulin (4%) in the diet of weanling rabbits showed no positive effects. On the other hand, Bovera et al (2010) reported that concentration of 1.0 g/kg MOS in the diet could reduce rabbit mortality and improve growth performance.…”
Section: Introductionmentioning
confidence: 97%
“…However, Bonai et al. () showed that Inulin (4%) in the diet of weanling rabbits showed no positive effects. On the other hand, Bovera et al.…”
Section: Introductionmentioning
confidence: 99%
“…This helps optimise the eubiosis, improves the digestion capacity and increases the animal health status (Attia et al, 2011a). Oligosaccharide-based prebiotics like inulin have been intensively examined as an alternative to antibiotics in growing rabbits (Maertens et al, 2004;Bonai et al, 2010) and rabbit does (Maertens et al, 2013). Radwan and Abdel-Khalek (2007) reported that galacto-oligosaccharides and MOS are able to fortify rabbits reared under high ambient temperatures by improving growth and health of growing rabbits.…”
Section: Introductionmentioning
confidence: 99%